KOMPETENSI PEDAGOGIK YANG DIMILIKI GURU KELAS TINGGI DI MI MA’ARIF NU 2 PANCASAN AJIBARANG - Susanti Susanti (Jurnal Penelitian Agama, 2018)
Abstract: The background of this research is that all teachers must have pedagogic competence in managing learners' learning, which includes learners' related understanding, planning and implementation of learning, evaluation of students' learning outcomes and the development of potential learners who are instructed by teachers in various activities according to their potential. This journal article is used as a reference in conducting research. The theoretical basis discussed in this article is Pedagogic Competence, High Class Teachers and Pedagogic Competencies of High Class Teachers in SD/MI. The purpose of this journal is to illustrate the management of learning by high school teachers through High Teacher Pedagogic Competencies in MI Ma'arif NU 2 Pancasan.The result of this study shows that high-class teachers should try as much as possible to educate their students, which includes: 1) understanding the learners in accordance with the characteristics, talents, intelligence and physical condition, 2) designing a learning device that matches the character of each learner, 3) implementing the design well in accordance with the student's condition and the state of the class, and 4) evaluating the learners' understanding in the cognitive, affective and psychomechanical aspects in evaluating the learning process and outcomes to be a benchmark of teacher's success in teaching and managing its learning, 5) understanding the final result of the evaluation to understand the student's thinking power and potential, and 6) developing students' potentials by actualizing their potentials in various academic and non academic activities. Keywords: competence, pedagogy, dan teacher.